Patterns and Causes of Female Labor Force Participation: An Age–Period–Cohort Analysis for Pakistan - Hina Amber; Bezawit Beyene Chichaibelu (Population Research and Policy Review, 2023)
Female participation rates in Pakistan's labor force are well below regional averages despite approximately 9 percent growth in the past three decades. To probe the underlying causes of the dynamics of female labor force participation in Pakistan, we use a synthetic panel constructed from nationally representative labor force surveys (1990–2017). The results indicate that the rising population share of working-age women does not account for changes in aggregate labor force participation rates. The age–period–cohort analysis demonstrates that for cohorts born since the 1900s, urban females' age effects follow a slight M-shaped curve, representing the child-raising phase during which females reduce labor force participation. The cohort effects signal an increase in the labor force participation of cohorts born after the 1950s. This is particularly the case for married females and females with less education that traditionally have weaker attachments to the labor market due to social norms. Therefore, understanding and identifying the factors that can have an effect on the inhibiting role of social norms are central to devising policies to foster female labor force participation.
Keywords: J16; J21; J22; 300; Demographic; Female labor force~participation; Synthetic panel; Age–period–cohort; Pakistan